Evaluating the Scope of Malignant Bone Tumor Using ADC Measurement on ADC Map. (19th July 2019) - Chen, Haisong; Wu, Zengjie; Xu, Wenjian; Pang, Jing; Jia, Meng; Dong, Cheng; Li, Xiaoli
Background: It is very important for surgeons to know the accurate borders of malignant bone tumors before they can precisely resect the tumors. The objective of the study is to investigate the usefulness of apparent diffusion coefficient value for estimating the extent of malignant bone tumor. Methods: VX2 tumor fragments were implanted into the tibiae of 30 rabbits. After 4 weeks, magnetic resonance plain scans were performed and then tumor specimens were cut into sagittal sections and partitioned into histology slices for dot-to-dot comparisons with microscopic findings. The sizes of the tumors measured separately on specimen, conventional magnetic resonance imaging sequences, and diffusion-weighted imaging (by measuring apparent diffusion coefficient value on apparent diffusion coefficient mapping) were compared statistically with each other. Results: The mean tumor sizes measured on specimen and apparent diffusion coefficient mapping (by calculating apparent diffusion coefficient value) were 5.20 ± 0.89 cm and 5.31 ± 0.87 cm, respectively; there was no significant difference between the 2 ( P > .05). The tumor sizes measured on T1WI, T2WI, T2WI with fat suppression were 4.82 ± 0.87 cm, 5.58 ± 0.87 cm, 5.63 ± 0.85 cm, respectively, and these values were significantly different from that measured on specimen (5.20 ± 0.89 cm, P < .05). Conclusion: The extent of the VX2 malignant bone tumor can be estimated accurately by measurement of apparent diffusion coefficient value.